Continuous hydrogen production from cofermentation of sugarcane vinasse and cheese whey in a thermophilic anaerobic fluidized bed reactor. (19th July 2018) - Ramos, Lucas Rodrigues; Silva, Edson Luiz
Abstract: The co-fermentation of vinasse and cheese whey (CW) was evaluated in this study by using two thermophilic (55° C) anaerobic fluidized bed reactors (AFBRs). In AFBR using vinasse and CW (AFBR-V-CW), the CW was added in increasing proportions (2, 4, 6, 8, and 10 g COD.L −1 ) to vinasse (10 g COD.L −1 ) to assess the advantage of adding CW to vinasse. By decreasing the hydraulic retention time (HRT) from 8 h to 1 h in AFBR-V, maximum hydrogen yield (HY), production rate (HPR), and H2 content (H2 %) of 1.01 ± 0.06 mmol H2 .g COD −1, 2.54 ± 0.39 L H2 .d −1 .L −1, and 47.3 ± 2.9%, respectively, were observed at an HRT of 6 h. The increase in CW concentration to values over 2 g COD.L −1 in AFBR-V-CW decreased the HY, PVH, and H2 %, with observed maximum values of 0.82 ± 0.07 mmol H2 .g COD −1, 1.41 ± 0.24 L H2 .d −1 .L −1, and 55.5 ± 3.7%, respectively, at an HRT of 8 h. The comparison of AFBR-V-CW and AFBR-V showed that the co-fermentation of vinasse with 2 g COD.L −1 of CW increased the HPR, H2 %, and HY by 117%, 68%, and 82%, respectively. Graphical abstract: Image 1 Highlights: Addition of cheese whey (2 g COD.L −1 ) to vinasse increased H2 yield (HY) by 82%. Excess cheese whey concentration decreased HY by lack of nitrogen. Decrease in hydraulic retention time (HRT < 6 h) decreased HY and production rate (HPR). Maximum HY (1.01 ± 0.06 mmol H2 .g COD −1 ) was observed in HRT of 6 h. H2 production in both reactors was dominated by acetic and butyric pathways.